Endophytic Bacteria Showing Antioxidant Property from Periwinkle [Catharanthus roseus (L.) G. Don] - Chauhan, B. P.; Singh, N. K.; Kaswan, V.; Soni, K. K.; Soni, N. V. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted in the year, April–December, 2020 at the Department of Microbiology, C. P. College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat, India to isolate and characterize promising antioxidant producing endophytic bacteria from periwinkle plant. Twenty four endophytic bacterial cultures derived from various parts of Catharanthus roseus (L.) G. Don were tested for total antioxidant capacity (TAC) and total phenolics content (TPC). The isolate R1 showed highest TAC (615.46 µg AAE mg-1 extract) followed by the isolate R2 (308.59 µg AAE mg-1 extract). Correlation coefficient observed between TAC and TPC was 0.7591, which shows that phenolic compounds were greatly responsible for antioxidant capacity of the bacterial isolates. 15 isolates showing higher TAC were studied for morphological and molecular characteristics. All the 15 isolates were rod shaped and were monobacillus. Nine isolates were Gram positive whereas 6 were Gram negative. 16S rDNA amplification using universal primers 27F and 27R produced a band of 1.5 kb. Restriction digestion of PCR products of all the isolates with tetracutter restriction enzymes AluI, TaqI, Hae III produced polymorphic diagnostic fingerprints. The dendrogram based on ARDRA profiling grouped the 15 bacteria into two groups (cluster A and cluster B) at a Jaccard’s similarity co-efficient of 0.83. Cluster A contained eleven bacterial isolates whereas cluster B had only four. The isolates R1 and R2 may serve as an excellent source of antioxidants and may be exploited for commercial production of antioxidants.